Islamic Financial Services Act (IFSA) 2013 and the Sharīʿah-compliance requirement of the Islamic finance industry in Malaysia - Mohamad Akram Laldin; Hafas Furqani (ISRA International Journal of Islamic Finance, 2018)
Purpose: This paper aims to observe the development of the Sharīʿah governance framework (SGF) and practice in Islamic financial institutions (IFIs) in Malaysia. Design/methodology/approach The study is a qualitative-based research. It uses various documents and content analysis approach to understand and analyze the structure, process and practice of SGF in IFIs in Malaysia. Findings It is found that the Central Bank of Malaysia, Bank Negara Malaysia, has attempted to develop a comprehensive framework of Sharīʿah governance for IFIs in Malaysia. The framework governs the practice of the industry, covers stakeholders' scope of duties and responsibilities and provides details on processes and procedures in the operations of IFIs to achieve the objective of Shari?ah compliance. To maintain the relevance of the SGF to the needs of the industry, the framework has also been updated recently in 2017. The amendments aim to strengthen the effectiveness of Shari?ah governance implementation within the Islamic finance industry. Originality/value This study attempts to comprehensively examine the evolution of the SGF Sharīʿah governance framework for IFIs in Malaysia. The Malaysian model of the SGF is unique and could be emulated by other countries in developing the Islamic finance industry in their respective jurisdictions.
Keywords: 330; Islamic finance; Malaysia; Sharīʿah compliance; Sharīʿah governance; Sharīʿah standards